(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Digital storytelling is a powerful educational tool that integrates multimedia elements to create narrative-driven experiences. This article explores the use of digital storytelling to enhance language learning, emphasizing its impact on linguistic competence, cultural understanding, and digital literacy skills. By engaging learners in the creation and presentation of digital stories, educators can promote language acquisition, creativity, and communication skills. The article discusses theoretical foundations, benefits, practical strategies, and case studies demonstrating the effectiveness of digital storytelling in language education.